Contemporary Issues in the Sociology of Death, Dying and Disposal - Jupp, Peter C. author. aut Link
XIX, 225 p.
Keywords: This book utilises a dynamic analysis of mortality to acknowledge shifts of emphasis in cultural and religious traditions. A central concern is the diversity of representations of death to be found within the varying cultural, religious, medical and legal systems of contemporary western societies. Since the construction of death mores has social implications, a major element of the book is an examination of the way in which groups and individuals employ specific representations of mortality in order to generate meaning and purpose for life and death.